A educação em direitos humanos como instrumento de consolidação dos direitos fundamentais e da democracia - Moreira, Laura Maria Ferreira (2020)
This study highlights human rights education as a means of realizing fundamental human rights and democracy today, considering in this approach the processes of discrimination and exclusion of the citizen, justifying this study by the importance of the theme, both in the national scenario international, in addition to the close relationship with the fundamental constitutional objectives and the possibility that human rights education can make a relevant contribution to democracy and the existing applicable regulations, as well as the capacity of human rights education to contribute to the realization of human rights. natural rights, especially in favor of excluded groups and minorities seeking effective responses in various types of conflicts that currently exist, demonstrating that education enables the modification of the individual, through the defense of their dignity, giving every citizen the possibility of knowing their own rights. The research methodology used to develop this work was based on a bibliographic review of scientific articles and other publications in academic databases such as SciELO and Capes, in addition to specialized books and periodicals.